Performance Analysis of a 5-DOF Robotic Arm by Implementing a Graphical User Interface - Nurul Muthmainnah Mohd Noor; Muhamad Safwan Sabin; Rohidatun Mahmod@Wahab (Malaysian Journal of Science and Advanced Technology, 2023)
Today, the topic of performance in industrial robotics is being addressed by researchers at a much faster pace than a few years ago. In 2023, there are a variety of applications for industrial robotics, such as agriculture, education, and the film industry. In this paper, the implementation of Graphical User Interface (GUI) as a controller input between an Android smartphone and the Arduino was discussed. This GUI was developed to help the user in controlling the robotic arm. For the movement of 5-degree motion of a robot, the concept of inverse kinematics (IK) was applied to the system. To test the performance of the robot, a simple test had done by drawing the basic shape by putting the pencil into the gripper. Then, these drawings were compared with the original by calculating the percentage error of the dimensions from the center to the outside. The result shows that the robotic arm is capable of performing all the tasks assigned to it and can also be controlled through the graphical user interface of a smartphone. Therefore, implementing Bluetooth Wi-Fi as a communication between smartphone and robot is a good way to study the performance of robots, especially for small and lightweight robotic arms.